PENGARUH PENAMBAHAN LIMBAH PLAFON PVC TERHADAP KARAKTERISTIK CAMPURAN ASPAL BETON AC-WC - AMIN, CHOIRUL; Arif, Samsul (NAROTAMA JURNAL TEKNIK SIPIL, 2023)
Asphalt is a material that is widely used in road construction. The use of asphalt materials is getting higher, but the asphalt materials used are increasingly expensive and limited, research was conducted as an effort to save asphalt materials with the addition of PVC ceiling waste, with the aim of determining the effect of adding PVC ceiling waste to AC-WC asphalt materials. The method used for study carried out in the laboratory with the Marshall test method then obtained the calculation results, namely the Marshall quotient. The characteristics of the AC-WC pavement mixture include density, voids in mineral aggregate (VMA), voids filled with bitumen (VFA), voids in the mix (VIM), stability, Marshall melting (flow), and Marshall Quotient (MQ). The results of research from 3 variations of mixtures of PVC ceiling waste used with varying values of 0%, 2%, 3%, and 4%. Of each variation of PVC ceiling waste mixture, all of them have met the technical specifications of Highways in 2018, but the most optimal mixture variation is found in the 2% variation with a stability value of 1689.75 kg, with a VMA value of 16.64%, VFA value of 79.60%, VIM value of 4.57%, flow value of 2.7 mm, and MQ value of 612.91 kg / mm, the variation content of 2% is declared the most effective for mixing AC-WC asphalt, so that the variety of added materials for PVC ceiling waste is most optimally used as a mixture of AC-WC asphalt with a penetration of 60/70. Keywords : AC-WC Asphalt, ASTM, PVC Ceiling Waste